PELATIHAN KADER POSYANDU MEMBUAT ABONLECIOUS (ABON LELE) SEBAGAI MAKANAN TAMBAHAN BALITA STUNTING - Ambar Wati, Desti (Poltekkes Kemenkes Bengkulu, 2025)
Stunting remains a significant health problem in Indonesia. Based on the 2023 Indonesian Health Survey, the prevalence of stunting reached 21.5%, exceeding the target of the National Medium-Term Development Plan (RPJMN) which targets 14% in 2024. The 2022 Indonesian Nutritional Status Survey also showed that Pringsewu Regency had a stunting prevalence of 16.2%. Stunting can be handled by providing Supplementary Food (PMT) based on modified local food ingredients, such as catfish floss. Abon, which is generally made from beef, can now be processed using various types of meat, including fish, to provide a variety of flavors and increase nutritional value. This community service activity was carried out in May 2024 in Pekon Wates, Pringsewu, targeting Posyandu cadres. Activities included socialization and demonstration of making catfish floss. The response from Posyandu cadres was very positive. This training in making catfish floss is expected to be an alternative solution in handling stunting. Posyandu cadres gain practical skills in processing catfish into nutritious shredded fish, and can educate the community about the importance of consuming nutritious food to support children's growth and development. Empowerment of posyandu cadres is expected to increase community knowledge and awareness in preventing stunting by providing affordable and easily processed protein sources